A Convexity Property for an Integral Operator on the Class SP(β). (10th January 2008) - Breaz, Daniel
Abstract : We consider an integral operator, F n ( z ), for analytic functions, f i ( z ), in the open unit disk, U . The object of this paper is to prove the convexity properties for the integral operatorF n ( z ), on the classS p ( β ) .